The Similar Effects of miR-512-3p and miR-519a-2-5p on the Promotion of Hepatocellular Carcinoma: Different Tunes Sung With Equal Skill - Rui, Tao; Zhang, Xueyou; Feng, Shi; Huang, Haitao; Zhan, Shaowei; Xie, Haiyang; Zhou, Lin; Ling, Qi; Zheng, Shusen (Frontiers in Oncology, 2020)
Although the therapeutic methods of hepatocellular carcinoma (HCC) have made great advances, the current situation is that HCC is the common malignancy. Our previous bioinformatic study presented that two members of C19MC (mir-512-1 and mir-519a-2) acted as crucial roles in the HCC progression. In this study, we first demonstrated that the miR-512-3p and miR-519a-2-5p, which were spliced from the mir-512-1 and mir-519a-2, were the functional mature miRNAs. Meanwhile, both miR-512-3p and miR-519a-2-5p were significantly upregulated in human HCC samples and HCC cell lines. The miR-512-3p and miR-519a-2-5p promoted the proliferation, invasion, and metastasis in vitro and in vivo. Moreover, the two miRNAs co-targeted the downstream tumor suppressors MAP3K2 and MAP2K4 and subsequently achieved the HCC progression. In the clinical cohort, high expression of miR-512-3p and miR-519a-2-5p acted as two risk factors for HCC recurrence and distinguished patients with poor tumor-free survival after radical resection. The integration of the two miRNAs into the AJCC staging system significantly improved the accuracy for the prediction of HCC recurrence. Our study suggests that miR-512-3p and miR-519a-2-5p have similar effects on the promotion of HCC progression. They can be robust markers for the prediction of HCC recurrence and therapy targets.